Experiments on sheathed cold‐formed steel beam‐columns. Issue 2 (1st September 2021) - Kyprianou, Constantinos; Kyvelou, Pinelopi; Gardner, Leroy; Nethercot, David A.
Abstract: An experimental study on sheathed cold‐formed steel C‐lipped columns (studs) with service holes in the web subjected to compression and major axis bending is presented in this paper. A total of 17 experiments was performed with both oriented strand board (OSB) and plasterboard used as the sheathing material and with varying connector spacing employed between the sheathing and the steel members. Material tests and geometric imperfection measurements were also undertaken. The tested specimens comprised a single 2.4 m long cold‐formed steel member sheathed on both sides and secured at its ends to top and bottom tracks. Eight pure compression tests with plasterboard and OSB sheathing and with the spacing of the connectors varying between 75 mm and 600 mm were initially performed. Specimens with OSB were then tested under pure bending and also under combined loading, by first applying a compressive load corresponding to the 75%, 50% or 25% of the predetermined axial resistance and then laterally loaded until failure. Reducing the spacing of the connectors from 600 mm to 75 mm resulted in up to 20% and 30% increases in capacity for the studs sheathed with OSB and plasterboard respectively.